Teacher leadership for social change in bilingual and bicultural education - Palmer, Deborah K., 1969- (Bristol, Blue Ridge Summit, PA : Multilingual Matters, 2018)
'Bilingual teachers must advocate for their students. Based on the experiences of Spanish-English bilingual teachers in Texas, this book aims to explore, define and understand bilingual teacher leadership. It examines what it means for bilingual teachers to become leaders, the kinds of support they need, and how they experience leadership' --
Includes bibliographical references and index.
Keywords: Educational leadership -- Texas; Multicultural education -- Texas; Education, Bilingual -- Texas; Social change -- Texas